HUBUNGAN POSISI MENYUSUI, FREKUENSI MENYUSUI, KEADAAN PUTING SUSU DENGAN BENDUNGAN ASI PADA IBU NIFAS DI PUSKESMAS SUNGAI PINANG KABUPATEN OGAN ILIR TAHUN 2024 - Kuryani, Tri; Eka Afrika; Erma Puspita Sari; Arie Anggraini (LPPM STIKes Mitra Adiguna, 2025)
Breast engorgement is a condition of blocked milk flow due to narrowing of the lactiferous ducts, incompletely emptied mammary glands, or abnormalities in the nipples. This study aims to determine the relationship between breastfeeding position, breastfeeding frequency, and nipple condition simultaneously with the occurrence of breast engorgement in postpartum mothers at the Sungai Pinang Community Health Center, Ogan Ilir Regency, in 2024. Data were obtained from 64 postpartum mothers during January–February 2024, with 8 mothers experiencing breast engorgement. This study used an analytical survey design with a cross-sectional approach to explain the relationship between breastfeeding position, breastfeeding frequency, and nipple condition (independent) with the occurrence of breast engorgement (dependent). The results of the bivariate analysis showed that the breastfeeding position was less than optimal at 23.4% (p = 0.004), the frequency of breastfeeding was not optimal at 25.0% (p = 0.000), and the nipple condition was abnormal at 18.8% (p = 0.001). There is a significant relationship between these three variables and the incidence of breast milk engorgement. It is recommended that community health centers actively provide education, counseling, and counseling on proper breastfeeding techniques, the importance of breastfeeding immediately after delivery, and an understanding of the causes and impacts of breast milk engorgement in postpartum mothers.